Comparación del proceso de enseñanza – aprendizaje, de un niño con síndrome de Down y un niño no Down de la Institución Educativa Franz Schubert. - Tapia Gordillo, Andrea Vanesa (2014)
This investigation tries ti establish differences frainning – learning ol a Down syndrome boy between a boy no Down with 5 and 6 years old. Know characteristics, qualities, develop by means of parameters. I have considered the pedagogics ideas of Peaget, Vygotsky and Montessori. They speak about the periods the children`s life. Piaget speaks about the stayes of cognitive developes from the birth to the adolescence. Vygotsky says the boy obtains his knowledges while his actuation in the environment. Montessori says the boy lears in a dynamic, entertaining, environment with motivation.